2013
DOI: 10.1080/19443994.2012.704718
|View full text |Cite
|
Sign up to set email alerts
|

Parametric equations for the variables of a steady-state model of a multi-effect desalination plant

Abstract: 2013) Parametric equations for the variables of a steady-state model of a multi-effect desalination plant, Desalination and WaterIn this work a steady-state model is developed of an MED plant. Its development and validation have been carried out by experimental data obtained from an MED pilot plant located at the Plataforma Solar de Almería (PSA), in the southeast of Spain. It is a vertical arrangement forward-feed MED plant with preheaters, which uses hot water as the thermal energy source. In order to run th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The cooling seawater is spilt into the big pool and part of the heat released by the condenser could increase its temperature during an experiment. To avoid that, a dry cooler is switched on, however sometimes it is insufficient [11]. Therefore, it is difficult to obtain a long-steady state in all its variables even though the MED plant has control mechanisms at its inputs.…”
Section: Description Of the Plantmentioning
confidence: 98%
See 3 more Smart Citations
“…The cooling seawater is spilt into the big pool and part of the heat released by the condenser could increase its temperature during an experiment. To avoid that, a dry cooler is switched on, however sometimes it is insufficient [11]. Therefore, it is difficult to obtain a long-steady state in all its variables even though the MED plant has control mechanisms at its inputs.…”
Section: Description Of the Plantmentioning
confidence: 98%
“…The current design specifications of the MED plant are shown in Table 1 [11]. All the tube bundles are made of 90-10 Cu-Ni with a 14 mm of outside diameter.…”
Section: Description Of the Plantmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors of this book carried out an evaluation of wet (evaporative water and once-through) and dry cooling technologies for different CSP + D configurations (with MED and RO desalination plants) in the Mediterranean area and the Arabian Gulf (Palenzuela et al 2013(Palenzuela et al , 2015. It was found that the use of evaporative water cooling was the most economical in terms of electricity production.…”
Section: Cooling Systems In Csp Plantsmentioning
confidence: 99%